2006
DOI: 10.3892/ijo.28.2.469
|View full text |Cite
|
Sign up to set email alerts
|

GTI-2501, an antisense agent targeting R1, the large subunit of human ribonucleotide reductase, shows potent anti-tumor activity against a variety of tumors

Abstract: GTI-2501 is a 20-mer oligonucleotide that is complementary to a coding region in the mRNA of R1, the large subunit of ribonucleotide reductase (RNR). In vitro studies, have demonstrated that GTI-2501 decreases mRNA and protein levels of R1 in a sequence-specific and dosedependent manner. Furthermore, GTI-2501 inhibits the growth of human lung, liver, ovary, brain, melanoma, breast and pancreatic tumor cells in colony forming assays. In vivo studies have shown that GTI-2501 significantly inhibits growth of huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 21 publications
2
60
0
Order By: Relevance
“…As shown in antisense DNA oligo targeting RRM1, was also able to inhibit tumor growth in vitro and in vivo. 27 It however should be noted that RRM1-specific siRNA is only effective in tumors that overexpress RRM1 (Fig. 2E), but not in gemcitabine-sensitive parent TC-1 tumors that do not overexpress RRM1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in antisense DNA oligo targeting RRM1, was also able to inhibit tumor growth in vitro and in vivo. 27 It however should be noted that RRM1-specific siRNA is only effective in tumors that overexpress RRM1 (Fig. 2E), but not in gemcitabine-sensitive parent TC-1 tumors that do not overexpress RRM1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that higher inherent levels of RRM2 expression is associated with resistance to a variety of anticancer agents, including gemcitabine, hydroxyurea, 2,2-difluorodeoxycytidine, and 5-FU [16,19,20]. Recently, several studies reported that the inhibition of endogenous RRM2 using phosphorothioate antisense oligonucleotides or siRNA decreases malignant cell proliferation, and enhances chemosensitivity [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…GTI-2040 is a 20-base phosphorothioate oligonucleotide that is complementary to a coding region in the mRNA of the R2 small subunit component of human ribonucleotide reductase [81]. Preclinical studies have demonstrated that GTI-2040 inhibits the growth of a variety of cancer cell lines and tumors in breast cancer models; it also has been shown to reduce metastasis of melanoma to the lungs [81].…”
Section: Gti-2040mentioning
confidence: 99%